2018
DOI: 10.3389/fpsyg.2018.02588
|View full text |Cite
|
Sign up to set email alerts
|

When Mindfulness Interacts With Neuroticism to Enhance Transformational Leadership: The Role of Psychological Need Satisfaction

Abstract: Transformational leadership is a popular and well-researched leadership style. Although much is understood about its positive consequences, less research has focused on antecedents of transformational leadership. In this research we draw upon self-determination theory and incorporate a self-regulatory approach to investigate if and how leader mindfulness influences transformational leadership. The analyses show that autonomy, competence and relatedness need satisfaction mediate between mindfulness and transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 113 publications
2
28
1
Order By: Relevance
“…Bass (1985) stated that transformational leaders focus on followers’ demands, motivate followers to realize the goals of the organization and encourage followers to pursue group interests and self-development. Recent research has found that mindfulness can positively influence TFL by fulfilling leaders’ need for autonomy, competence and relatedness (Decuypere et al, 2018). Transformational leaders achieve the aforementioned goals through their charisma or idealized influence, inspiration or inspirational motivation, intellectual stimulation and individualized consideration (Bass, 1985, 1995; Bass and Avolio, 1990).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Bass (1985) stated that transformational leaders focus on followers’ demands, motivate followers to realize the goals of the organization and encourage followers to pursue group interests and self-development. Recent research has found that mindfulness can positively influence TFL by fulfilling leaders’ need for autonomy, competence and relatedness (Decuypere et al, 2018). Transformational leaders achieve the aforementioned goals through their charisma or idealized influence, inspiration or inspirational motivation, intellectual stimulation and individualized consideration (Bass, 1985, 1995; Bass and Avolio, 1990).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Following this theoretical logic, we suggest that when employees with different levels of neuroticism experience resource loss, they are more likely to show diverse perceptions of this adverse event, thus adopting differentiation strategy. More specifically, employees with high neuroticism act more sensitive to resource loss (i.e., WNG) for lack of psychological resources, and they are likely to constantly reinforce resource loss and magnify negative perceptions of themselves (Li et al, 2016;Lu et al, 2017;Decuypere et al, 2018). Consequently, they tend to be in the grip of psychological distress, such as anxiety, tension, and emotional instability.…”
Section: Moderating Effect Of Neuroticismmentioning
confidence: 99%
“…In addition research shows that when the disposition for mindfulness is already high, training no longer has a major additional effect. So specifically if a leader is (1) rather distracted and is generally categorized as 'not mindful', or (2) scores high on neuroticism (Decuypere et al 2019), training can be an interesting investment (Feltman et al 2009).…”
Section: Recommendations For Practicementioning
confidence: 99%
“…It would also be interesting for future research to focus more on mapping the effect of mindfulness on the communication process between leaders and their employees (Decuypere et al 2019). Qualitative research shows that mindfulness helps to listen better and communicate more clearly (Kearney et al 2013;Frizzell et al 2016).…”
Section: New Trends and Future Researchmentioning
confidence: 99%